The indirect effect of distributive justice in the relationship between pay structure and work attitudes and behavior - Ismail, Azman; Ong, Guatleng; Tan, Cheekiong; Ibrahim, Zalina; Ajis, Mohd Na'eim; Dollah, Noor Faizah (2009)
This study investigates the effect of distributive justice and pay structure on work attitudes and behaviors (i.e., job satisfaction and organizational commitment).A survey method used, gathering 189 usable questionnaires from academic employees who have worked in Malaysian public community colleges.The outcomes of stepwise regression analysis showed two important outcomes: first, relationship between pay structure and distributive justice significantly correlated with job satisfaction.Second, relationship between pay structure and distributive justice significantly correlated with organizational commitment. This result demonstrates that the inclusion of distributive justice in the analysis has increased the effect of pay structure on both job satisfaction and organizational commitment.Further, the result confirms that distributive justice acts as a full mediating variable in the pay system models of the organizational sector sample.In addition, implications and limitations of this study, as well as directions for future research are elaborated.